Layered construction of integrated sulfur-bridged CoNi-S/rGO architecture for enhanced electrochemical energy storage - Aboelazm, Eslam Atef Abdelaziz; Khe, Chengseong; Grätz, Sven; Chong, Kwok Feng; Mohamed Shuaib, Mohamed Saheed; Hegazy, Mohamed Barakat Zakaria (Elsevier B.V., 2024)
Transition metals chalcogenides (TMCs) have been recognised so far with their high Faradic activity, making them promising candidates for efficient charge transfer electrodes. However, their tendency to aggregate hindered their potential applications in supercapacitors. This study introduces a novel cathode material composed of CoNi-sulfides (CoNi-S) nanostructured flakes and reduced graphene oxide (rGO) sheets designed to be connected through additional sulfur atoms to enhance their conductivity and electroactive surface area for hybrid supercapacitors. Remarkable results were realised by forming a layered structure of CoNi-S/rGO in which rGO sheets wrap CoNi-S flakes. Interestingly, the CoNi-S/rGO composite exhibited a specific capacitance of 3308F g−1 (1654C g−1) at 1 A g−1, outperforming the performance of a single CoNi-S component, which recorded 2155F g−1 (1077.5C g−1) at identical conditions. Both materials demonstrated exceptional high-rate capabilities, retaining about 70 % of their capacitance even at an elevated current density of 10 A g−1. In a two-electrode coin cell system, the device showcased a high energy density of 50.2 Wh kg−1 at a power density of 750 W kg−1. It maintained an impressive 84 % capacitance retention after enduring 35,000 cycles. These remarkable findings hold significant promise for advanced energy storage applications, marking substantial progress forward in hybrid supercapacitor technology.